Analgesic and anti-inflammatory effect of Clausena suffruticosa root extract in animal model - Rahman, M. A.; Chakma, J. S.; Islam, S.; Rana, M. S.; Ahmed, N. U. (Journal of Scientific Research, 2011)
The aim of the study was to evaluate the analgesic and anti-inflammatory effects of Clausena suffruticosa root extract. The effect of different concentrations of ethanolic root extract were studied in animal model using acetic acid induced writhing response, formalin induced pain, hot plate method for analgesic activity in Swiss Albino mice and carrageenan induced paw edema for anti-inflammatory action in Wister Albino rat. The extract reduced writhing response 20% by 0.5g/kg, 57.6% by 1.5g/kg and 78% by 2 g/kg and showed significant analgesic activity as determined by formalin induced pain and hot plate method. In the carrageenan induced paw edema, the extract at a dose of 0.5, 1.0 and 2.0 g/kg showed the highest inhibition 17.23%, 26.30% and 42.46%, respectively, at the 4th hour of administration. The results indicate that the extract shows promising analgesic effect in chemical models of nociception (not related to the opioid system) and anti-inflammatory effect.